Perspectives on delivering sexual and reproductive health and rights information and services to young people: focus group discussions with civil society organizations in the Democratic Republic of Congo - Landry Egbende; Viviane Mayala; Branly Mbunga; Nina Viberg; Mala Ali Mapatano; Tobias Alfvén; Eva Åkerman (Global Health Action)
Background Universal access to sexual and reproductive health and rights (SRHR) is fundamental to achieving the Sustainable Development Goals due to its impact on gender equality as well as women’s health and survival. In the Democratic Republic of Congo, there are many civil society organizations (CSOs) that are involved in raising awareness of SRHR issues and providing SRHR services to young people. Objective: The aim of this study was to explore the challenges and enabling factors CSOs experience regarding the delivery of SRHR services to young people. Methods We conducted a qualitative study via focus group discussions with CSOs in Kinshasa. Two focus groups comprising women and two comprising men, with approximately 10 participants in each group, were held. The interview transcripts were subjected to an inductive thematic analysis. Results Young people’s barriers to SRHR information and services were described as multi-layered, linked to individual, community, societal, institutional, and health system levels. The most common barrier in delivering SRHR information was the widespread view of sexuality as a taboo subject in communities and churches as well as in young people’s families. Despite the obstacles that CSOs faced, the results also demonstrate that CSOs have found creative ways to reach out and offer SRHR information to young people. Conclusion It is essential to acknowledge the role of CSOs in the advancement of gender equality, and it is important to put policies into place that can overcome cultural, religious, and familial barriers to young people’s access to SRHR information.